KARAKTER KEPEMIMPINAN TERHADAP KEBERLANGSUNGAN ORGANISASI - Danang Nugroho; Siti Robiah Aldawiyah; Pintia Deviana Auliansyah; Sahrul Hidayat; Revi Regina; Syifa Nabila (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Every leader must have a unique character, habits, and personality that makes him different from others through his actions and style. This style and lifestyle will definitely shape his behavior and teaching methods. The leader is used as a role model for his subordinates. Because the leader must be able to set an example to be imitated by his subordinates. Leadership with character is characterized by four main characteristics, namely: honest, farsighted, inspiring, and competent. The combination of these four characteristics creates reliability.